2022
DOI: 10.1108/k-07-2021-0614
|View full text |Cite
|
Sign up to set email alerts
|

How do businesses achieve sustainable success and gain a competitive advantage in the green era?

Abstract: PurposeTo attain green economic efficiency, small, micro and medium-sized firms must follow environmental paradigms. This research aims to discover the relationship between green intellectual capital, green entrepreneurial orientation, green marketing, green organizational culture and competitive advantage strategies to attain sustainable manufacturing business success.Design/methodology/approachToday, many companies have accepted their responsibilities, that their operations should not harm the environment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 66 publications
0
18
0
1
Order By: Relevance
“…The data analysis with the help of PLS-SEM is found to be more beneficial and relevant to previous research (e.g. Yusoff et al, 2019;Can Saglam et al, 2021;Mansoor et al, 2021;Wang et al, 2022;Asiaei et al, 2022).…”
Section: Source(s): Authors Workmentioning
confidence: 72%
See 2 more Smart Citations
“…The data analysis with the help of PLS-SEM is found to be more beneficial and relevant to previous research (e.g. Yusoff et al, 2019;Can Saglam et al, 2021;Mansoor et al, 2021;Wang et al, 2022;Asiaei et al, 2022).…”
Section: Source(s): Authors Workmentioning
confidence: 72%
“…GIC is the integration of environmental knowledge sources as well as the firm's green competencies to obtain a competitive advantage. GIC facilitates the attainment of knowledge of an organization for conducting green management (Wang et al, 2022). In addition, GIC provides full compliance with international environmental legislation as well as addresses the customers' environmental awareness (Mansoor et al, 2021).…”
Section: Green Intellectual Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, various researchers have suggested that companies get a sustained competitive edge by implementing strategies that leverage their internal strengths by responding to environmental opportunities while neutralizing external threats and avoiding the weaknesses [39][40][41][42]. The study on sources for sustained competitive derives from the perspective of isolating a firm's opportunities and threats [43].…”
Section: Model For Sustained Competitive Advantagementioning
confidence: 99%
“…Hasil pengujian hipotesis ke enam menunjukkan bahwa green organizational culture tidak memberikan pengaruh positif terhadap green competitive advantage. Temuan ini tidak sejalan dengan penelitian Widiyati & Murwaningsari (2021), C. H. Wang (2019), dan W. Wang et al, (2022). Green organizational culture belum dapat memberikan pengaruh terhadap green competitive advantage karena walaupun perusahaan telah mempunya komitmen terhadap pengelolaan lingkungan, tetapi perusahaan belum melakukan penerapan secara maksimal terhadap manajemen lingkungan dan perlindungan lingkungan, sehingga perusahaan belum memiliki karakteristik atau ciri khas lingkungan hijau yang sulit ditiru oleh para pesaingnya.…”
Section: Pengaruh Green Organizational Culture Terhadap Green Competi...unclassified